A microchip flow‐chamber assay screens congenital primary hemostasis disorders. Issue 2 (5th December 2020) - Nakajima, Yuto; Yada, Koji; Ogiwara, Kenichi; Furukawa, Shoko; Shimonishi, Naruto; Shima, Midori; Nogami, Keiji
Abstract: Background: Von Willebrand disease (VWD) and platelet function disorders (PFDs) are congenital bleeding disorders caused by primary hemostasis defects. Platelet function tests are time‐consuming and require considerable amounts of blood sample, and there have been no easy‐to‐use assays for assessing platelet function quickly and sensitively. We report the usefulness of a microchip flow‐chamber system (T‐TAS ® ) for detecting and/or predicting clinical severity in patients with VWD type 1 and type 2N and platelet storage pool disease. Here, we developed an application of a screening assay for primary hemostasis disorders. Methods: Microchips coated with collagen (PL‐chip) and collagen/thromboplastin (AR‐chip) were utilized to evaluate platelet thrombus formation (PTF) at high shear and fibrin‐rich PTF at low shear, respectively, in whole blood samples from 22 patients with VWD (16 type 2A, four type 2B, two type 3) and four patients with PFDs (two BSS, two Glanzmann thrombasthenia). The time‐to‐increase by 10 kPa (T10 ) was calculated from flow pressure curves. Also, whole blood‐induced platelet aggregation was assessed using Multiplate ® analysis. Results: PL‐chip T10 values ≥10 min successfully distinguished patients with all types of VWD and PFDs from healthy controls, irrespective of age, bleeding scores, and von Willebrand factor levels. However, AR‐chip assay incompletely distinguished between type 2A patients and healthy ones. Multiplate analysis permitted screening of PFDs and type 3 VWD, but values in type 2A partially overlapped with those in controls. PL‐chip assay did not reflect the clinical severity in these patients. Conclusions: T‐TAS with PL‐chip could be a quick screening tool for congenital primary hemostasis disorder, VWD, and PFDs.